Fitchburg Railroad Company Passenger Depot, Causeway Street, ca. 1860-90 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west of the Fitchburg Railroad Company Passenger Depot, located on the southwest corner of Beverly and Causeway Streets. A large clock adorns the facade of the depot, which faces southeast towards Causeway Street. Electricity lines and poles line the sidewalk along the depot's northeast elevation and Beverly Street. A carriage is parked in front of the entrance to the depot, and people can be seen standing on the southwest corner of Causeway and Beverly Streets. A man walking across Causeway Street is included in the photograph. Copyprint. Designed by George M. Dexter 5 7/8 x 7 1/16, 7 x 8 13/16 overall Photographs